Detyrosinated microtubule arrays drive myofibrillar malformations in mdx muscle fibers - Harriot, Anicca D.; Altair Morris, Tessa; Vanegas, Camilo; Kallenbach, Jacob; Pinto, Kaylie; Joca, Humberto C.; Moutin, Marie-Jo; Shi, Guoli; Ursitti, Jeanine A.; Grosberg, Anna; Ward, Christopher W. (Frontiers in Cell and Developmental Biology, 2023)
Altered myofibrillar structure is a consequence of dystrophic pathology that impairs skeletal muscle contractile function and increases susceptibility to contraction injury. In murine Duchenne muscular dystrophy (mdx), myofibrillar alterations are abundant in advanced pathology (>4 months), an age where we formerly established densified microtubule (MT) arrays enriched in detyrosinated (deTyr) tubulin as negative disease modifiers impacting cell mechanics and mechanotransduction. Given the essential role of deTyr-enriched MT arrays in myofibrillar growth, maintenance, and repair, we examined the increased abundance of these arrays as a potential mechanism for these myofibrillar alterations. Here we find an increase in deTyr-tubulin as an early event in dystrophic pathology (4 weeks) with no evidence myofibrillar alterations. At 16 weeks, we show deTyr-enriched MT arrays significantly densified and co-localized to areas of myofibrillar malformation. Profiling the enzyme complexes responsible for deTyr-tubulin, we identify vasohibin 2 (VASH2) and small vasohibin binding protein (SVBP) significantly elevated in the mdx muscle at 4 wks. Using the genetic increase in VASH2/SVBP expression in 4 wk wildtype mice we find densified deTyr-enriched MT arrays that co-segregate with myofibrillar malformations similar to those in the 16 wk mdx. Given that no changes in sarcomere organization were identified in fibers expressing sfGFP as a control, we conclude that disease-dependent densification of deTyr-enriched MT arrays underscores the altered myofibrillar structure in dystrophic skeletal muscle fibers.